Proteostasis in striatal cells and selective neurodegeneration in Huntington’s disease - Margulis, Julia; Finkbeiner, Steven (Frontiers in Cellular Neuroscience, 2014)
Selective neuronal loss is a hallmark of neurodegenerative diseases, including Huntington’s disease (HD). Although mutant huntingtin, the protein responsible for Huntington’s disease, is expressed ubiquitously, a subpopulation of neurons in the striatum is the first to succumb. In this review, we examine evidence that protein quality control pathways, including the ubiquitin proteasome system, autophagy, and chaperones, are significantly altered in striatal cells. These alterations may increase the susceptibility of striatal cells to mutant huntingtin-mediated toxicity. This novel view of HD pathogenesis has profound therapeutic implications: protein homeostasis pathways in the striatum may be valuable targets for treating Huntington’s disease and other misfolded protein disorders.